Efektifitas Penggunaan Metode Pembelajaran Bercerita dalam Meningkatkan Perilaku Sosial Siswa Madrasah Ibtidaiyah di Kota Bengkulu - Diana Riyanti; Faisal Ahmad Akbar; Kamal Karazi; Iin Nurjanah; Deko Rio Putra (UIN Fatmawati Sukarno Bengkulu, 2025)
Abstract: The use of the storytelling learning method is still difficult among students, because students' interest in reading is still relatively low. The purpose of this study is to analyze the effectiveness of the use of storytelling learning methods in improving the social behavior of Madrasah Ibtidaiyah students in Bengkulu City. Using a descriptive qualitative method. The results of the study show that the storytelling method is one of the ways of speaking, providing learning experiences and honing students' literacy skills orally which is designed in play activities and fun for students, useful in the formation of character and good behavior for students. Social behavior is a person's action in the form of the result of relationships between individuals and the surrounding environment. Thus, it can be concluded that the storytelling method is considered effective in improving students' social behavior, because storytelling can make students comfortable, calm and happy and can help students in their imagination. By listening to stories, students do not feel advised and dictated by parents and teachers, but the moral messages conveyed in stories are strongly imprinted in the memory of students and students can behave and behave according to the content of the story. So that it can be suggested to improve students' social behavior, then increase the effectiveness of the use of storytelling methods in learning at madrasas.Keywords: Effectiveness, Storytelling Learning Methods, Social Behavior, Madrasah Ibtidaiyah in Bengkulu City. Abstrak: Penggunaan metode pembelajaran bercerita masih sulit dikalangan siswa, karena minat baca siswa masih tergolong rendah. Tujuan penelitian ini untuk menganalisis efektifitas penggunaan metode pembelajaran bercerita dalam meningkatkan perilaku sosial siswa Madrasah Ibtidaiyah di Kota Bengkulu. Menggunakan metode kualitatif deskriptif. Hasil penelitian menunjukkan bahwa metode bercerita merupakan salah satu cara bertutur kata, pemberian pengalaman belajar dan mengasah keterampilan literasi siswa secara lisan yang dirancang dalam kegiatan bermain dan menyenangkan bagi siswa, berguna dalam pembentukan karakter dan perilaku baik bagi siswa. Perilaku sosial merupakan suatu tindakan seseorang berupa hasil hubungan antar individu dengan lingkungan sekitarnya. Dengan demikian dapat disimpulkan bahwa metode bercerita dianggap efektif dalam meningkatkan perilaku sosial siswa, karena bercerita dapat membuat siswa nyaman, tenang sekaligus senang dan dapat membantu siswa dalam berimajinasi. Dengan mendengarkan cerita, siswa tidak merasa dinasehati dan di dekte oleh orang tua dan guru, namun pesanpesan moral yang disampaikan dalam cerita kuat terpatri dalam ingatan siswa dan siswa dapat bersikap dan berperilaku sesuai isi cerita. Sehingga dapat disarankan untuk meningkatkan perilaku sosial siswa, maka tingkatkan efektifitkan penggunaan metode bercerita dalam belajar di madrasah.Kata kunci: Efektifitas, Metode Pembelajaran Bercerita, Perilaku Sosial, Madrasah Ibtidaiyah di Kota Bengkulu.